Quality of Life in patients with nonalcoholic fatty liver disease: Structure and related factors focusing on illness uncertainty. Issue 3 (11th March 2021) - Ozawa, Naoki; Sato, Kazuki; Sugimura, Ayumi; Maki, Shigeyoshi; Tanaka, Taku; Yamamoto, Kenta; Ito, Takanori; Ishizu, Yoji; Kuzuya, Teiji; Honda, Takashi; Ishigami, Masatoshi; Fujishiro, Mitsuhiro; et al.
Abstract: Aim: Patients with nonalcoholic fatty liver disease (NAFLD) have a low quality of life (QOL) and illness uncertainty. This study examined the structure of QOL and associated factors, including illness uncertainty, among individuals with NAFLD. Methods: A cross‐sectional survey was conducted using a self‐administered questionnaire for outpatients with NAFLD. QOL was measured using the Short Form‐8. Dietary habits, physical activity level, illness uncertainty, health locus of control, and knowledge of NAFLD were assessed. Path analysis was used to study the associated factors of QOL and their structure, including uncertainty of disease. Results: Path analysis of 168 NAFLD patients indicated that a high Physical Component Summary score on the Short Form‐8—representing physical QOL—was predicted by a body mass index <25 kg/m 2 and high educational level. A high Mental Component Summary score—representing mental QOL—was predicted by being male, good dietary habits, low illness uncertainty, and presence of consultants. The model showed satisfactory goodness‐of‐fit without being rejected by the chi‐square test (goodness‐of‐fit index = .947, adjusted goodness‐of‐fit index = .917, comparative fit index = .967, root mean square error of approximation = 0.023). Conclusions: Nurses need to work closely with NAFLD patients as consultants, providing adequate information about the causes, treatments, and dietary habits, and focusing on the individual's perception of health. This could reduce illness uncertainty and contribute to the improvement of QOL.